Safety Goggles Myopi as a Worker Protector with Myopic Eye Complaints - Naufal Ilham Saputra; Ramadhani, Husnul Kirom; Violin Margaretha Puspita Ningrum; Amrina Rosyadah; Muslikha Nourma Rhomadhoni (Universitas Nahdlatul Ulama Surabaya, 2024)
ABSTRACT The number of workers who have near-sightnedness and is supported by a lack of compliance in use of PPE for comfort reasons causes the potential for work accidents. This research aimed to reduce the number of eye injuries and become an innovation in safety glasses and PPE for workers complaints of myopia. This study used an analytical descriptive method with a cross-sectional study design, which was carried out from June to October 2022. The total respondents in this study were 60 respondents. Furthermore, this study used an instrument, namely a survey questionnaire through a comprehensive Google Form. From the survey, 55% of respondents used glasses, 53.3% of respondents experienced complaints of myopia, 18.3% of respondents have worn glasses before work, 20% of respondents were required to wear protective glasses while working, and 80% of respondents showed interest in